2016
DOI: 10.4103/2229-516x.186962
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of integrated teaching module in pharmacology among medical undergraduates

Abstract: Context:Over the years with advancement of science and technology, each subject has become highly specialized. Teaching of medical students has still remained separate in various departments with no scope of integration in majority of medical institutes in India. Study was planned to have an experience of integration in institute and sensitize faculty for integrated teaching–learning (TL) method.Aims:To prepare and test effectiveness of integrated teaching module for 2nd year MBBS student in pharmacology and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 15 publications
1
24
0
1
Order By: Relevance
“…In a study by Preeti P Yadav and colleagues, 75 % of students reinforce similar findings. 16 Another study demonstrates that active learning modules are associated with better understanding of abstract concepts (77%) and more teacher-student interaction. 17 In a published research, 94% students reported that interactive sessions facilitate interest in subject and motivate for more study.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Preeti P Yadav and colleagues, 75 % of students reinforce similar findings. 16 Another study demonstrates that active learning modules are associated with better understanding of abstract concepts (77%) and more teacher-student interaction. 17 In a published research, 94% students reported that interactive sessions facilitate interest in subject and motivate for more study.…”
Section: Discussionmentioning
confidence: 99%
“…21 Effective implementation resulted in improved critical reasoning skills and better understanding of concepts by the students. 22,23 Most of the students mentioned in the study that field visits to pharmaceutical industry, clinical research organization and preclinical testing laboratories helps in better understanding of pharmacology. Due to various reasons, we were unable to arrange for field visits for this group of students.…”
Section: Discussionmentioning
confidence: 99%
“…1 Integrated teaching reduces the amount of information overload associated with the traditional curriculum, where there is more focus on the delivery of detailed information and minimal emphasis is given to the link between various subjects and their clinical application. 1,3 Moreover, integrated learning encourages learning in a comprehensive manner and reduces boundaries among various subjects and their departments while encouraging coordination among departments, including providing faculty members with multiple learning opportunities. 2,3 In addition, it discourages repetition of the same topic across different subjects.…”
mentioning
confidence: 99%
“…1,3 Moreover, integrated learning encourages learning in a comprehensive manner and reduces boundaries among various subjects and their departments while encouraging coordination among departments, including providing faculty members with multiple learning opportunities. 2,3 In addition, it discourages repetition of the same topic across different subjects. 1 Realizing the scope and the merits of the integrated curriculum, medical colleges have begun to initiate implementation.…”
mentioning
confidence: 99%
See 1 more Smart Citation